HUBUNGAN RISIKO ERGONOMI DENGAN KELUHAN MUSCULOSCELETAL DISOREDER (MSDs) PADA KARYAWAN PT. INTIDRAGON SURYATAMA KABUPATEN MOJOKERTO - Mujiadi; Anndy Prastya; Siti Rachmah; Henry Sudiyanto (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2023)
Unnatural work attitude is a discrepancy between the dimensions of the tool and work station and body size. In a long time there will be an accumulation of complaints and ends in muscle injury. The research objective is to find out complaintsMusculosceletal Disorderbecause of the ergonomic attitude of workers at PT. Intidragon Suryatama. This research is studycross sectional, a semiquantitative approach. Primary data collection through direct observationon the spot field observations, taking photos or pictures, interviews using the Nordic Body Map questionnaire on 96 workers. From 96 respondents, 31 respondents worked in ergonomic positions and 65 respondents worked not ergonomically. Of the 65 respondents whose work position was not ergonomic, as many as 6 respondents (10%) workers complained of mild MSDs complaints, most of the 49 respondents (75%) had moderate MSDs complaints and as many as 10 respondents (15%) had high MSDs complaints. The company's Occupational Health and Safety always creates an ergonomic work environment, provides ergonomic seating for employees.